2009
DOI: 10.1186/1471-2148-9-130
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of a tree fern Alsophila spinulosa: insights into evolutionary changes in fern chloroplast genomes

Abstract: Background: Ferns have generally been neglected in studies of chloroplast genomics. Before this study, only one polypod and two basal ferns had their complete chloroplast (cp) genome reported. Tree ferns represent an ancient fern lineage that first occurred in the Late Triassic. In recent phylogenetic analyses, tree ferns were shown to be the sister group of polypods, the most diverse group of living ferns. Availability of cp genome sequence from a tree fern will facilitate interpretation of the evolutionary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
133
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 43 publications
18
133
0
Order By: Relevance
“…Most of the codons prefer A or T at the third position. The analysis of the composition for the codons showed that A+T content at the third position was 72.6%, similar to what was reported for Alophila (8) and Panax schinseng Nees (1).…”
Section: Gene Content and Codon Usagesupporting
confidence: 63%
See 1 more Smart Citation
“…Most of the codons prefer A or T at the third position. The analysis of the composition for the codons showed that A+T content at the third position was 72.6%, similar to what was reported for Alophila (8) and Panax schinseng Nees (1).…”
Section: Gene Content and Codon Usagesupporting
confidence: 63%
“…Therefore and In addition to phylogenetic analysis based on plastidic genomes, it is imperative to understand the chloroplast genome in order to logically design our next generation transplastomics. Accordingly, chloroplast genomes of many species have been sequenced (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Overall, 44.05, 2.06, and 6.73% of the genome sequence encode proteins, tRNAs, and rRNAs, respectively, whereas the remaining 47.15% of the genome is non-coding and filled with introns and intergenic spacers. Similar to other cp genomes Gao et al, 2009;Yang et al, 2010), the Z. latifolia cp genome is AT-rich (61.02%), and the values vary slightly among defined non-coding, protein-coding, tRNA, and rRNA sequences, with A+T contents of 64.35, 60.52, 47.21, and 45.03%, respectively. The four rRNA genes are all positioned in the IRs.…”
Section: Resultsmentioning
confidence: 89%
“…Importantly, it has been suggested that other chloroplast introns are targeted by MatK as well: firstly, several chloroplast genomes of parasitic plants and ferns have lost trnK, but have retained a free-standing matK reading frame, suggesting additional tasks for MatK, presumably in splicing other introns (4,5,(11)(12)(13); and secondly, loss of chloroplast translation leads to loss of splicing for some, but not all chloroplast introns, suggesting that a chloroplast reading frame is required for splicing these multiple introns (7,15,16). As there are no other candidates for RNA processing factors in the well-described and small chloroplast genome, it was suggested that matK is responsible for splicing these introns.…”
mentioning
confidence: 99%